Decentralized Control using Flocking Rules - Ribeiro, R. (2020)
Multi-Agent Systems (MAS) - a network composed of mobile agents with the objective of converging to high-value positions. No centralized infrastructure - implies the need for a decentralized algorithm to compute the actuation. Applicable to surveillance - a group of vigilant robots that want to periodically visit sites to be monitored. Typical solutions use consensus algorithms , can cope with asymmetric wireless links. Consensus algorithms can be made to work with noise in the measurements